Design and Application of Activity Value Management (AVM): The Case of Taiwan Soka Association - Wu, Anne (The journal of CESNUR, 2023)
This study explores the essence and major theoretical innovations of Activity Value Management (AVM), which aims to assist organizations in effectively utilizing their resources. In the first part, it presents AVM essence and main theoretical innovations. In the second part, it discusses the application of AVM to Taiwan Soka Gakkai, Taiwan's affiliate of Soka Gakkai International. In the third part, it shows how AVM may assist managerial decision-making in the case of a non-profit organization. Finally, it lists different benefits the use of AVM may offer to non-profit organizations such as Taiwan Soka Gakkai.